2014
DOI: 10.1007/s00438-014-0935-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the expansin gene superfamily reveals Brassica rapa-specific evolutionary dynamics upon whole genome triplication

Abstract: Chinese cabbage (Brassica rapa subsp. pekinensis) is an economically important vegetable that has encountered four rounds of polyploidization. The fourth event, whole genome triplication (WGT), occurred after its divergence from Arabidopsis. Expansins (EXPs) are cell wall loosening proteins that participate in cell wall modification processes. In this study, the impacts of WGT on the B. rapa expansin (BrEXP) superfamily were evaluated. Whole genome screening of B. rapa identified 32 loci coding 53 expansin gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…About 500 RING finger genes were identified in the Arabidopsis genome (Table S4); therefore, up to 1500 RING finger genes could be produced by the WGT event in the B. rapa genome. However, only 715 RING finger genes were identified in the B. rapa genome (Table S1), suggesting that more than 50% of duplicated RING finger genes were either lost or fixed by nonfunctionalization (silencing) after WGT565758. Similar results were also observed for other gene families in Brassica species5859.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…About 500 RING finger genes were identified in the Arabidopsis genome (Table S4); therefore, up to 1500 RING finger genes could be produced by the WGT event in the B. rapa genome. However, only 715 RING finger genes were identified in the B. rapa genome (Table S1), suggesting that more than 50% of duplicated RING finger genes were either lost or fixed by nonfunctionalization (silencing) after WGT565758. Similar results were also observed for other gene families in Brassica species5859.…”
Section: Discussionsupporting
confidence: 70%
“…However, only 715 RING finger genes were identified in the B. rapa genome (Table S1), suggesting that more than 50% of duplicated RING finger genes were either lost or fixed by nonfunctionalization (silencing) after WGT565758. Similar results were also observed for other gene families in Brassica species5859. In fact, our analysis of syntenic relationships between RING finger genes of B. rapa and A. thaliana showed that, only in 50 cases, the triplicated copies were well retained on all the three subgenomes (LF, MF1 and MF2) of B. rapa , while in 146 cases, only two of the three triplicated copies were retained, and in 294 cases, only one of the three triplicated copies was retained in B. rapa genome.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the EXPA members (82%) had three exons, while EXLB genes presented the largest number of exons, ranging from four to six, similar to Malus x Domestica and G. max (Zhang et al 2014b; Zhu et al 2014). The EXLA members had the same gene structure (4-exon/3-intron) in both Arachis species which differs from the usual 5-exon/4-intron EXLA structure of other plants (Ding et al 2016; Krishnamurthy et al 2014; Sampedro et al 2005). …”
Section: Resultsmentioning
confidence: 92%
“…Although we did not detect orthologs for some genes involved in flavonoid biosynthesis (e.g., TT4, TT6 , and AHA10 ), in accordance with the fact that the excessive gene loss is typical after polyploidy formation in eukaryotes (Sankoff et al, 2010; Wang et al, 2011), we identified orthologs of many of these genes by querying the Brassica genome databases with the sequences of A. thaliana genes involved in flavonoid biosynthesis. In addition, it has been widely suggested that the genome structures are highly conserved among Brassica species (Krishnamurthy et al, 2014; Thamilarasan et al, 2014; Dong et al, 2016). Each of the gene copies was found to be distributed in orthologous blocks by collinearity analysis between the A and C subgenomes (Figure 2).…”
Section: Discussionmentioning
confidence: 99%